Natural Feed Selection For Supporting The Rearing Of Banggai Cardinal Fish (Pterapogon kauderni) In Lini Aquaculture Training Center (Latc) Bali - Hulu, Hasrat Damai; Julyantoro, Pande Gde Sasmita; Kasa, I Wayan (Metamorfosa: Journal of Biological Sciences, 2020)
This research was aimed to obtain the kind of proper natural food and the optimum dose of feeding in order to support the rearing of banggai cardinal fish breeding. This research used completely randomized design and was conducted during September to December 2016. The kinds of natural food examined were trash fish, abalone (Haliotis glabra) , and squid (Loligo pealei) . After we found the most preferable food, the examination upon its dose was conducted under 10%, 20% and 30% of the fish weight. The 45 fish sampel have average length and weight of 3 cm and 0,47 g, respectively. Fish were reared in aquarium 95 cm x 45 cm x 35 cm. The foods were given three times a day. The research results show that abalone was mostly consumed compared to other two foods about 0,11 g/fish a day. The result of examining dose showed that the highest rate of fish growth was found under the dose of 30% which resulted 2,07 cm in length, 0,34 g in weight and the dose of 20% which resulted 2,07 cm in length, 0,33 g in weight. The statistical test result showed that the treatment under the dose of 30% and 20% was not significantly different ( P >0,05). Base on this study, it can be concluded that abalone is the proper natural food that supports the rearing of banggai cardinal fish with optimum dose of 20 % of fish weight per day.   Keywords:       Banggai cardinal fish, Natural Feed, Lini Aquaculture Training Center.